A clinico-radiological and pathological profile of lung cancer patients presented to All India Institute of Medical Sciences (Patna) - Rai, Deependra K; Kumar, Abhisheka; Kumar, Abhishek; Kumar, Ashish; Thakur, Somesh (Eastern Journal of Medical Sciences, 2017)
Background: Lung cancer is one of the most common cancers and cause of cancer-related deaths worldwide. The clinicopathological profile of lung cancer has shown marked regional and geographical variation. Majority of the patients have locally advanced or disseminated disease at presentation and are not candidates for surgery. Objective: The aim of this study was to evaluate the clinico-radiological and pathological profile of lung cancer patients and difference in histopathology between smoker and non-smoker. We also assessed yield of the various diagnostic procedures used for confirmation of lung cancer. Materials and Methods: A total of 30 patients diagnosed between May 1, 2016, and December 31, 2016. The complete demographic profile, smoking status, clinical, radiological, and diagnostic details were recorded in the study. Data were entered and analyzed using SPSS software. Results: A total of 30 patients (19 male and 11 female) included in our study with mean age of 55.26 years. Cough (80%) and dyspnea (80%) were the most common symptom and mass (86%), pleural effusion (53.3%) was the most common radiological presentation of patients. Clubbing and hemoptysis both was found only in 8 out of 30 (26%) patients. Adenocarcinoma (46.6%) was the most common histopathological type followed by squamous cell carcinoma (16.6%) and small cell carcinoma (13.3%). The majority of patients (60%) presented in Stage 4. Computed tomography guided biopsy had better yield in compare to ultrasonography guided (80% vs. 70.8%). Bronchoscopic procedure had lowest yield (38.8%). Conclusion: The clinicopathological profile of lung cancer has changed in last few years, especially in the increase in adenocarcinoma incidence, and now it is the most common cause in both smokers and non-smoker.